Estimating Technical Efficiency of Academic Departments of a Philippine Higher Education Institution - Gono, Jr., Exequiel Reposposa (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The main thrust of this research is to measure the relative technical efficiency of the six (6) colleges of San Pedro College from school year 2004-2014. The technical efficiency of the academic units can be derived based on its ability to produce the optimum number of output (number of research outputs, number of graduates, and number of community extension conducted) based on a given set of inputs (budget allocation and ratio of the full-time and part-time faculty) using data envelopment analysis. The Nursing/Respiratory Therapy Department is consistent as the highest for the ratio of full-time to part-time faculty while the lowest ratio was observed by Medical Laboratory Sciences Department in 2016, Arts and Sciences in 2015 and Accounting and Business in 2014. In terms of technical efficiency, all departments are technically-efficient during 2014. The Nursing/Respiratory Therapy Department, Physical Therapy Department and Medical Laboratory Sciences Department did not obtain 100% efficiency. In 2016, only the Accounting and Business Management Department did not obtain full technical efficiency score. Further, using the Tobit model, the age of the department, number of baccalaureate teachers, proportion of faculty members with doctorate degree with those who are masters’ degree holders, and the dean’s qualification were found to be insignificant as sources of inefficiency.